Interfacial synthesis of a large-area coordination polymer membrane for rewritable nonvolatile memory devices. Issue 35 (2nd June 2020) - Zhang, Zepu; Nie, Yijie; Hua, Weiwei; Xu, Jingxuan; Ban, Chaoyi; Xiu, Fei; Liu, Juqing
Abstract : Stable nonvolatile memory devices with a high ON/OFF current ratio have been realized based on a large-area two-dimensional coordination polymer membrane. Abstract : The facile synthesis of large-area coordination polymer membranes with controlled nanoscale thicknesses is critical towards their applications in information storage electronics. Here, we have reported a facile and substrate-independent interfacial synthesis method for preparing a large-area two-dimensional (2D) coordination polymer membrane at the air–liquid interface. The prepared high-quality 2D membrane could be transferred onto an indium tin oxide (ITO) substrate to construct a nonvolatile memory device, which showed reversible switching with a high ON/OFF current ratio of 10 3, good stability and a long retention time. Our discovery of resistive switching with nonvolatile bistability based on the substrate-independent growth of the 2D coordination polymer membrane holds significant promise for the development of solution-processable nonvolatile memory devices with a miniaturized device size.